Economic Institutions and the Location Strategies of European Multinationals in their Geographical Neighbourhood - Andrea Ascani; Riccardo Crescenzi; Simona Iammarino (London School of Economics and Political Science (LSE), European Institute, 2015)
This paper investigates how the location behaviour of Multinational Enterprises (MNEs) is shaped by the economic institutions of the host countries. The analysis covers a wide set of geographically proximate economies with different degrees of integration with the 'Old' 15 European Union (EU) members: New Member States, Accession and Candidate Countries, as well as European Neighbourhood Policy (ENP) countries and the Russian Federation. The paper aims to shed new light on the heterogeneity of MNE preferences for the host countries' regulatory settings (including labour market and business regulation), legal aspects (i.e. protection of property rights and contract enforcement) and the weight of the government in the economy. By employing data on 6,888 greenfield investment projects, the randomcoefficient Mixed Logit analysis here applied shows that, while the quality of the national institutional framework is generally beneficial for the attraction of foreign investment, MNEs preferences over economic institutions are highly heterogeneous across sectors and business functions.
Keywords: F23; P33; L20; R30; 330; Multinational Enterprises; Economic Institutions; Location Choice; European Union